Nexus of COVID-19 and diabetes pandemics: Global public health lessons. (June 2020) - Bergman, Michael; Jagannathan, Ram; Narayan, K.M. Venkat
Abstract: Individuals with non-communicable diseases (NCDs) such as diabetes are susceptible to communicable diseases (CDs) as the current COVID-19 pandemic illustrates. The co-occurrence of diabetes as well as other co-morbid conditions with COVID-19 augurs greater risk for severe outcomes and mortality. Hence, NCD and CD pandemics are closely linked and require global efforts to thwart and disrupt their nexus before the next viral outbreaks occurs. This will require steadfast dedication and resolve to address NCDs previously committed to by the global community.